Temporal dysfunction in traumatic brain injury patients: primary or secondary impairment? - Mioni, Giovanna; Grondin, Simon; Stablum, Franca (Frontiers in Human Neuroscience, 2014)
Adequate temporal abilities are required for most daily activities. Traumatic brain injury (TBI) patients often present with cognitive dysfunctions, but few studies have investigated temporal impairments associated with TBI. The aim of the present work is to review the existing literature on temporal abilities in TBI patients. Particular attention is given to the involvement of higher cognitive processes in temporal processing in order to determine if any temporal dysfunction observed in TBI patients is due to the disruption of an internal clock or to the dysfunction of general cognitive processes. The results showed that temporal dysfunctions in TBI patients are related to the deficits in cognitive functions involved in temporal processing rather than to a specific impairment of the internal clock. In fact, temporal dysfunctions are observed when the length of temporal intervals exceeds the working memory span or when the temporal tasks require high cognitive functions to be performed. The consistent higher temporal variability observed in TBI patients is a sign of impaired frontally mediated cognitive functions involved in time perception.